2020
DOI: 10.3389/fspor.2020.594501
|View full text |Cite
|
Sign up to set email alerts
|

Access to Physical Activity and Sport and the Effects of Isolation and Cordon Sanitaire During COVID-19 for People With Disabilities in Scotland and Canada

Abstract: People with a disability are more at risk of experiencing inequalities in relation to sporting and physical activity opportunities, COVID-19 and the resulting restrictions stand to exacerbate these inequalities. This research directly contributes toward the World Health Organization, global research roadmap priority to explore “the impact of restrictive public health measures (e.g., quarantine, isolation, cordon sanitaire).” Social loneliness and social isolation have a significant impact on the health and wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…As expected, an association was found between measures of mental wellbeing and physical activity, with negative changes to physical activity levels linked to poorer wellbeing. Similar links have been reported in other COVID-19 research and particularly in the countries of interest ( Ingram et al, 2020 ; Kamyuka et al, 2020 ; Koohsari et al, 2021 ; Makizako et al, 2021 ; Yamada et al, 2020 ). Our data does not consider causation and so it may be that experiencing greater negative mood and feelings of social isolation are associated with participants changing their physical activity levels ( Robbins et al, 2018 ; Werneck et al, 2019 ), or that shifts to lower levels of physical activity have affected mental wellbeing ( Cerin et al, 2009 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As expected, an association was found between measures of mental wellbeing and physical activity, with negative changes to physical activity levels linked to poorer wellbeing. Similar links have been reported in other COVID-19 research and particularly in the countries of interest ( Ingram et al, 2020 ; Kamyuka et al, 2020 ; Koohsari et al, 2021 ; Makizako et al, 2021 ; Yamada et al, 2020 ). Our data does not consider causation and so it may be that experiencing greater negative mood and feelings of social isolation are associated with participants changing their physical activity levels ( Robbins et al, 2018 ; Werneck et al, 2019 ), or that shifts to lower levels of physical activity have affected mental wellbeing ( Cerin et al, 2009 ).…”
Section: Discussionsupporting
confidence: 87%
“…Specific to the current investigation, studies in Japan have shown decreases in physical activity during the period of mild lockdown in individuals over 40 years of age ( Makizako et al, 2021 ; Yamada et al, 2020 ) and in a stratified sample of participants between 20 and 59 ( Koohsari et al, 2021 ). In Scotland, participants who were engaged in a lot less physical activity during lockdown reported higher negative mood scores ( Ingram et al, 2020 ), whilst in a qualitative study, people with disabilities in Scotland and Canada indicated that their mental wellbeing had been impacted by the lack of physical activity ( Kamyuka et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the World Health Organization (2020) warned that some disabled people may be at a greater risk of contracting COVID-19 for several reasons: it may be impractical to implement sanitizing or social distancing protocols due to physical difficulty enacting taken-for-granted hygiene measures such as washing hands; a lack of or inaccessible facilities; the need for physical assistance by a carer; or because one may need to touch surfaces to gain feedback from the environment or to physically support themselves. In a sporting context for example, wheelchair users likely require more physical distance from others, yet space restrictions in sport clubs and facilities, as well as the behaviors of other people, may not allow for safe distancing (Kamyuka et al, 2020). Kamyuka et al (2020) also illustrated that disabled people with mobility issues harbored concerns about the likelihood of making unavoidable contacts with potentially unsanitized surfaces when away from their homes.…”
Section: Covid-19 Disability and The 'Extremely Clinically Vulnerable...mentioning
confidence: 99%
“…In a sporting context for example, wheelchair users likely require more physical distance from others, yet space restrictions in sport clubs and facilities, as well as the behaviors of other people, may not allow for safe distancing (Kamyuka et al, 2020). Kamyuka et al (2020) also illustrated that disabled people with mobility issues harbored concerns about the likelihood of making unavoidable contacts with potentially unsanitized surfaces when away from their homes.…”
Section: Covid-19 Disability and The 'Extremely Clinically Vulnerable...mentioning
confidence: 99%
See 1 more Smart Citation